2018
DOI: 10.1186/s12284-018-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cold-tolerant locus in rice (Oryza sativa L.) using bulked segregant analysis with a next-generation sequencing strategy

Abstract: BackgroundCold stress can cause serious abiotic damage that limits the growth, development and yield of rice. Cold tolerance during the booting stage of rice is a key factor that can guarantee a high and stable yield under cold stress. The cold tolerance of rice is controlled by quantitative trait loci (QTLs). Based on the complex genetic basis of cold tolerance in rice, additional efforts are needed to detect reliable QTLs and identify candidate genes. In this study, recombinant inbred lines (RILs) derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 54 publications
0
45
2
1
Order By: Relevance
“…However, despite further progress in the molecular genetic dissection of LTS tolerance in rice, few of them were confirmed to be stable QTLs across environments (Fujino et al 2008;Ji et al 2010;Li et al 2013;Cui et al 2013;Kim et al 2014;Zhu et al 2015). With the development of advanced genomics and molecular marker technology, six QTLs (qCTS-9, qCT8, qCTB7, qCTB3, qCT-3-2, and qCTB10-2) have been finemapped via a map-based cloning approach and only two QTLs (Ctb1 and CTB4a) have been cloned and functionally conferred to LTS (Kuroki et al 2007;Saito et al 2010;Zhou et al 2010;Shirasawa et al 2012;Zhu et al 2015;Li et al 2018;Sun et al 2018). However, even with the different genetic backgrounds of rice germplasm, QTLs for stage-specific cold tolerance were mapped on different locations on the 12 chromosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite further progress in the molecular genetic dissection of LTS tolerance in rice, few of them were confirmed to be stable QTLs across environments (Fujino et al 2008;Ji et al 2010;Li et al 2013;Cui et al 2013;Kim et al 2014;Zhu et al 2015). With the development of advanced genomics and molecular marker technology, six QTLs (qCTS-9, qCT8, qCTB7, qCTB3, qCT-3-2, and qCTB10-2) have been finemapped via a map-based cloning approach and only two QTLs (Ctb1 and CTB4a) have been cloned and functionally conferred to LTS (Kuroki et al 2007;Saito et al 2010;Zhou et al 2010;Shirasawa et al 2012;Zhu et al 2015;Li et al 2018;Sun et al 2018). However, even with the different genetic backgrounds of rice germplasm, QTLs for stage-specific cold tolerance were mapped on different locations on the 12 chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with the different genetic backgrounds of rice germplasm, QTLs for stage-specific cold tolerance were mapped on different locations on the 12 chromosomes. Several researchers have been using different temperature regimes ranging from 4 to 28°C for cold tolerance screening while employing diverse rice germplasm and bi-parental mapping populations, and they have reported several vegetative-and reproductive-stage QTLs for cold tolerance (Fujino and Matsuda 2010;Suh et al 2010;Jiang et al 2011;Park et al 2013;Zhu et al 2015;Pan et al 2015;Shakiba et al 2017;Zhao et al 2017;Liang et al 2018;Sun et al 2018;Xiao et al 2018). Through genome-wide association studies (GWAS) approaches, 97 QTLs were identified for LTS tolerance at the germination stage (Pan et al 2015;Sales et al 2017;Schläppi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While cold damage can occur at any growth stage, chilling injury at the early seedling stage can lead to slow growth, delayed crop maturity, poor establishment, and decreased yield [40]. In a universal screening method developed by Shirasawa et al [41], rice plants are maintained in a cold deep-water irrigated pool during the entire booting stage, and the completion, spikelet fertility is used to determine cold tolerance in the population [42]. To evaluate cold tolerance, the parameters of germination percent, germination index, root, shoot, and seedling length, and seedling vigor are usually observed [43].…”
Section: Consequences and Mitigation Strategies Of Abiotic Stresses 3mentioning
confidence: 99%
“…Despite various strategies, adopted to develop cold tolerant rice cultivars, the unexpected chilling snaps caused 5%-10% reduction in yield annually and occasionally it could go up to 20%-40% [8,11]. In 24 rice producing countries, including the major areas of Japan, Korea and China, there are about 15 million hectares rice fields under threat of low temperature stress where yield losses are estimated about at three-five million tons per year [12][13][14].…”
Section: Introductionmentioning
confidence: 99%